Will Teacher-AI Collaboration Enhance Teaching Engagement? - Lai-Jian Ding; Jia-Min Li; Bei-He Hui (Behavioral Sciences)
Against the backdrop of the widespread integration of Artificial Intelligence (AI) into educational practices, collaboration between teachers and AI is profoundly influencing teaching behavior. Drawing on the Conservation of Resources Theory, this study constructs and tests a model examining the impact of teacher-AI collaboration on teaching engagement, with a focus on the mediating role of technological self-efficacy and the moderating role of perceived organizational support. Based on empirical data collected through a survey in China, the results reveal that teacher-AI collaboration significantly and positively predicts teaching engagement. Furthermore, technological self-efficacy mediates this relationship, suggesting that AI collaboration enhances teaching engagement by boosting teachers’ confidence in using technology. In addition, perceived organizational support positively moderates the effect of teacher-AI collaboration on technological self-efficacy, forming a moderated mediation model. This research enriches the understanding of teacher behavior in the context of AI integration and offers practical implications for educational institutions seeking to optimize AI adoption strategies and enhance teacher motivation.